Burden of proof: a historical and theoretical analysis of some aspects of the following concepts in relation to the interpretation of Section 82 of Act 58 of 1962: income, assessment, objection and appeal - Rubinsztein, Aron Natan (Centre for Law and Society, 2026)
A clear understanding of Section 82 of the Income Tax Act No 58 of 1962 [the Act] is of great practical consequence toothed tax consultant. Indeed, many a well chartered voyage: In the uncertain stormy ocean of taxation litigation has floundered on some deep hidden Jagged edge of the iceberg “burden of proof”. It is unfortunate that scant attention has been given to section 82 by our authorities. The latest edition of Meyerowitz [1991], "the bible of tax consultant" does not have "burden of proof" or "onus of proof" in its index. Section 1892 deals with onus of proof in 5 lines. It cites three cases the latest of which was decided in 1958.